2008
DOI: 10.1158/1055-9965.epi-08-0238
|View full text |Cite
|
Sign up to set email alerts
|

Salt and Gastric Adenocarcinoma: A Population-Based Cohort Study in Norway

Abstract: Background: Gastric adenocarcinoma is the second leading cause of cancer death worldwide. It has been suggested that consumption of salted foods is associated with increased risk of this cancer, but the results of the few available prospective studies are contradictory. Methods: A population-based, prospective cohort study in Nord-Trondelag County in Norway during 1984 to 2002 addressed dietary salt intake in relation to risk of gastric adenocarcinoma. In 1984 to 1986, all adult county residents were invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
4
11
0
Order By: Relevance
“…This review revealed that some previous studies reported increased risk of advanced lesions (dysplasia or gastric cancer) with increased salt intake [12,13,15,17,19,20,23,27,28,30,31,33,34,37,38,40,41,42,43], consistent with our study, while others did not observe an association [14,16,17,20,21,24,25,26,29,30,31,32,35,36,43]. The differences in the estimates of salt intake on gastric precancerous lesions and/or gastric cancer from previous studies may have been due to potential effect modification by H. pylori infection, that were not accounted for in previous studies, but were in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This review revealed that some previous studies reported increased risk of advanced lesions (dysplasia or gastric cancer) with increased salt intake [12,13,15,17,19,20,23,27,28,30,31,33,34,37,38,40,41,42,43], consistent with our study, while others did not observe an association [14,16,17,20,21,24,25,26,29,30,31,32,35,36,43]. The differences in the estimates of salt intake on gastric precancerous lesions and/or gastric cancer from previous studies may have been due to potential effect modification by H. pylori infection, that were not accounted for in previous studies, but were in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In our review of the literature, we found 30 (19 case-control, 10 cohort, and one cross-sectional) [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43] epidemiological studies that estimated the effect of salt intake on gastric precancerous lesions and/or gastric cancer and provided data to estimate the effect of salt intake on gastric precancerous lesions or cancer. This review revealed that some previous studies reported increased risk of advanced lesions (dysplasia or gastric cancer) with increased salt intake [12,13,15,17,19,20,23,27,28,30,31,33,34,37,38,40,41,42,43], consistent with our study, while others did not observe an association [14,16,17,20,21,24,25,26,29,30,31,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects who preferred very salty food in diet had a more than 30-fold risk, compared to those preferring to non-salty food, which was in agreement with previous studies reporting that salt was a risk factor for gastric cancer (Nazario et al, 1993;Ramon et al, 1993;Tsugane et al, 2004). Although there was inconsistency regarding results of the association between salted meat and gastric cancer in literatures (Sjödahl et al, 2008;Keszei et al, 2012;Van Den Brandt et al, 2013), recent reviews summarized that increased consumption of processed meat including salted meat was significantly associated with gastric cancer Zhu et al, 2013). Another study conducted in a high risk area of gastric cancer in northwest of China also suggested long-term exposure to salted pork might result in repeated gastric mucosal damage and repair, and finally in severe dysplasia and malignancy (Yuan et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
“…These foods may contain carcinogenic N-nitroso compounds, in addition to a high level of salt (Scanlan, 1983). Although some previous studies have reported that salt or salted food was associated with an increased risk of gastric cancer Kim et al, 2010;Peleteiro et al, 2011), others showed weak or nonsignificant relationships (Sjödahl et al, 2008;Keszei et al, 2012). In addition, not much information has been available on etiological factors for gastric cancer in this high risk area, since no epidemiological studies were conducted there.…”
Section: Salt Processed Food and Gastric Cancer In A Chinese Populationmentioning
confidence: 97%